Efficacy of cognitive behavior language therapy for aphasia following stroke: Implications for language education research - Akabogu, Josephine (Medicine (Baltimore), 2019)
BACKGROUND/OBJECTIVE: Evidence from previous research has shown that the incidence of aphasia following a stroke is high in Nigeria and other countries, and there is a call for intervention programs. The objective of the current study was to investigate the efficacy of cognitive behavior language therapy (CBLT) on aphasia following a stroke. METHODS: The study was designed as a group randomized trial, which involved treatment and no-treatment control procedures. The participants of the study were 86 patients who had experienced aphasia following a stroke. The Porch Index of Communicative Ability (PICA) and Speech-Language Unhelpful Thoughts and Beliefs Scale (SLUTBS) were the measures used in the study. The repeated measures analysis of variance procedure, with Partial eta squared [Image: see text] , adjusted R(2), mean, standard deviation, and upper/lower limit was followed in analyzing the data collected in the study. RESULTS: The CBLT intervention significantly reduced aphasia following a stroke and significantly reduced speech-language and unhelpful thought and beliefs among aphasic stroke patients exposed to the treatment intervention when compared with the no-treatment control group. CONCLUSION: Based on the findings of the study, language educators, speech and language pathologists and therapists in education institutions, hospitals, and rehabilitation centers should adopt the principles of CBLT used in the current study to help them improve communication ability among aphasia stroke patients.